The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4141/cjps2013-084
|View full text |Cite
|
Sign up to set email alerts
|

SlPMEI, a pollen-specific gene in tomato

Abstract: 2014.SlPMEI, a pollen-specific gene in tomato. Can. J. Plant Sci. 94: 73Á83. Pectin is one of the main components of plant cell walls, and its biosynthesis is controlled by pectin methylesterase (PME). Pectin methylesterase inhibitors (PMEIs) are key regulators of PME. We report here the cloning and characterization of a novel Solanum lycopersicum L. PMEI gene, SlPMEI. RT-PCR studies of leaf, seed, fruit, flower, and flower organs confirmed that SlPMEI is expressed specifically in pollen. Promoter analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…SlCRK1 , a cysteine-rich receptor-like kinase, plays a critical role in pathogen protection and programmed cell death 45 . Pectin methylesterase inhibitor ( SlPMEI ) acts as a key regulator of pectin methylesterase (PME) 46 . LePRK3 , a pollen-specific receptor kinase gene, may take part in perceiving extracellular cues during pollen tube growth 47 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SlCRK1 , a cysteine-rich receptor-like kinase, plays a critical role in pathogen protection and programmed cell death 45 . Pectin methylesterase inhibitor ( SlPMEI ) acts as a key regulator of pectin methylesterase (PME) 46 . LePRK3 , a pollen-specific receptor kinase gene, may take part in perceiving extracellular cues during pollen tube growth 47 .…”
Section: Resultsmentioning
confidence: 99%
“…All of these genes showed a trend of downregulation in the transgenic lines, suggesting that SlOFP20 may control the mRNA accumulation of these pollen-specific genes to impact pollen development. In addition, previous studies revealed that many pollen-specific cis-acting elements, including the pollen-specific activation-related elements POLLEN1LELAT52 and the late pollen gene g10-related elements, were enriched in the promoter regions of two pollen-specific genes, SlCRK1 45 and SlPMEI 46 . Promoter-GUS chimeric expression experiments have been used to confirm that the promoters of SlCRK1 45 and SlPMEI 46 exhibit strong pollen-specific activity in the transgenic Arabidopsis and tomato plants.…”
Section: Discussionmentioning
confidence: 99%
“…Further, we assessed the expression of tomato pollen-specific genes involved in the pollen development in WT and SlGLO1 -silenced lines. SlCRK1 is one of the cysteine-rich receptor-like kinases, is important in pathogen defense and programmed cell death 33 ; Pectin methylesterase inhibitor (SlPMEI) is key regulators of pectin methylesterase (PME) 34 ; Pollen-specific receptor kinases gene LePRK3 is likely to be involved in perceiving extracellular cues during pollen tube growth 35 ; Exogenous rapid alkalinization factor (SlPRALF) acts as a negative regulator of pollen tube elongation within a specific developmental window 36 and LAT52 may play a role during germination or early tube growth 37 . The quantitative PCR results showed that these genes were all down-regulated by more than 90% in SlGLO1 -silenced lines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies about two pollen-specific genes including SlCRK1 and SlPMEI showed that their promoters region possess lots of pollen-specific cis-acting elements, such as, the pollen-specific activation-related elements POLLEN1LELAT52 (Lat52, AGAAA) and late pollen gene g10-related elements (G10, GTGA) 33 34 . Kim et al 33 34 also confirmed promoters of SlCRK1 and SlPMEI have strong pollen-specific activity in the homozygous transgenic plants of tomato. Similarly, we analyzed putative cis-acting elements within the SlGLO1 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Arabidopsis has been widely used to effectively characterize the cis -elements of the anther/pollen-specific promoters for homologous and heterologous crop plant species ( Swapna et al, 2011 ; Kim et al, 2014 ; Gao et al, 2016 ). In our study, the activities of pBnaC.SP6 deletions were analyzed in Arabidopsis .…”
Section: Discussionmentioning
confidence: 99%